Plasma Exosomes Derived From Patients With End-Stage Renal Disease and Renal Transplant Recipients Have Different Effects on Vascular Calcification - Lin, Xiao; Zhu, Ting; Xu, Feng; Zhong, Jia-Yu; Li, Fuxingzi; Shan, Su-Kang; Wu, Feng; Guo, Bei; Zheng, Ming-Hui; Wang, Yi; Xu, Qiu-Shuang; Liao, Xiao-Bo; et al. (Frontiers in Cell and Developmental Biology, 2021)
End-stage renal disease (ESRD) patients usually develop extensive and progressive vascular calcification, and lots of calcification inhibitors as well as pro-calcifying factors are involved in the process. However, the mechanisms of vascular calcification in ESRD patients are still ill-defined. In the present study, we found that the plasma exosomes derived from ESRD patients (ESRD-Ex) promoted calcification of vascular smooth muscle cells (VSMCs) significantly, while plasma exosomes from renal transplant recipients (RTR-Ex) could partially attenuate VSMCs calcification. Moreover, the protein concentration of ESRD-Ex was significantly higher than plasma exosomes from the normal health control group (Nor-Ex) and RTR-Ex, and the content of both matrix gla protein (MGP) and Fetuin-A, the calcification inhibitors, were prominently lower in ESRD-Ex than those in Nor-Ex. The content of Annexin-A2, one of the calcification promoters, was significantly higher in ESRD-Ex and RTR-Ex than that in Nor-Ex. But, bone morphogenetic protein (BMP-2) and receptor activator for nuclear factor-κB ligand (Rankl) had no significant difference among the three groups. In addition, the content of Fetuin-A in RTR-Ex was higher than that in ESRD-Ex, though it was still lower than in Nor-Ex. Furthermore, the levels of both Fetuin-A and MGP in plasma exosomes were negatively while the levels of Annexin-A2 in plasma exosomes was positively correlated to coronary artery calcification scores (CACS). These results indicated that ESRD-Ex significantly promoted VSMCs calcification while renal transplantation could partially attenuate the pro-calcification effect of exosomes. Fetuin-A and MGP were decreased but Annexin-A2 was increased in ESRD-Ex, and renal transplantation could increase the level of Fetuin-A rather than MGP.